National climate, agriculture and socio-economic development policies and plans formulated with the use of scenarios across six global regions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Climate change impacts bring great uncertainty, raising the need to plan for the future. As the impacts of climate change are complex and far-reaching, it can be extremely difficult to foresee exactly what the consequences will be, and how they will affect different regions and sectors. However, by bringing together relevant stakeholders and brainstorming "what if" ideas of possible future scenarios, policy makers can prepare themselves for a variety of potential challenges. Including stakeholders from diverse backgrounds can avoid blindspots focused on a single vision of the future.